Implicit-Explicit Scheme for the Allen-Cahn Equation Preserves the Maximum Principle (Journal of Computational Mathematics, 2018)
It is known that the Allen-Chan equations satisfy the maximum principle. Is this true for numerical schemes? To the best of our knowledge, the state-of-art stability framework is the nonlinear energy stability which has been studied extensively for the phase field type equations. In this work, we will show that a stronger stability under the infinity norm can be established for the implicit-explicit discretization in time and central finite difference in space. In other words, this commonly used numerical method for the Allen-Cahn equation preserves the maximum principle.
Keywords: Allen-Cahn Equations; Implicit-explicit scheme; Maximum principle; Nonlinear energy stability.